(3GdEaUGM Yf eYGfi GdUMGMs - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3CKfGA GdMOjK GdKGdK ef eSfO eYGhjI Hf CHj SajGf bhdg hHLejY GSeGFg GdMSfi cGdQMef hGdQMje hGdMi hHZjQgG s
(3BNQgG (B:s
(3hGdCUd ai bhdg GUWai GMJai hGdWGA eHOdI Yf JGA hGdeYfi Efg GUWai UGajkG Hf UGa MJi GfJgi Edi gGTe YHO GdeWdH Ke YHO Gddg BNQ GdeLdO GdQGHY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs